2000
DOI: 10.4141/p99-080
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal weed control and crop-year NPK fertilization improves lowbush blueberry (Vaccinium angustifolium Ait.) production

Abstract: . 2000. Herbicidal weed control and crop-year NPK fertilization improves lowbush blueberry (Vaccinium angustifolium Ait.) production. Can. J. Plant Sci. 80: [351][352][353][354][355][356][357][358][359][360][361]. Past research has shown that fertilizer applied in the vegetative year can increase yield, but not always. Fertilizer applied in the crop year without weed control also has been shown to increase yield. The present study, conducted on a natural lowbush blueberry stand for 8 yr, compared the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
44
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 18 publications
7
44
0
6
Order By: Relevance
“…In addition, average second crop yields in 54 harvest sets since 1985 were 71.58% of first crop yields in a commercial 3-yr management program (David Dickinson, personal communication). In this study, fertilizer applications resulted in increased crop yields under both management cycles, and also increased soil levels of P and K. Penney and McRae (2000) also reported yield increases from fertilizer applications. These results are in contrast to the results of a number of fertilizer studies on wild blueberries within the region (Eaton 1988(Eaton , 1994Eaton et al 1997;Sanderson and Eaton 2004).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, average second crop yields in 54 harvest sets since 1985 were 71.58% of first crop yields in a commercial 3-yr management program (David Dickinson, personal communication). In this study, fertilizer applications resulted in increased crop yields under both management cycles, and also increased soil levels of P and K. Penney and McRae (2000) also reported yield increases from fertilizer applications. These results are in contrast to the results of a number of fertilizer studies on wild blueberries within the region (Eaton 1988(Eaton , 1994Eaton et al 1997;Sanderson and Eaton 2004).…”
Section: Discussionmentioning
confidence: 77%
“…The current trial was established on the plots of a previous experiment (Penney and McRae 2000) conducted between 1983 and 1991 at the Atlantic Cool Climate Crop Research Centre's Blueberry Substation in Avondale, Newfoundland and Labrador (lat. 47°25′N; long.…”
Section: Experimental Design and Field Managementmentioning
confidence: 99%
“…Some negative responses were reported to be due to the stimulation of weeds by the applied fertilizer (Chandler 1943;Smagula and Ismail 1981). Recent research by Penney and McRae (2000) indicates that a lack of response to fertilizer may be related to timing of application. They showed that fertilizer applied in the vegetative year did not increase yield, but when applied in the crop year, increased production by approximately 40% over that with weed control alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), Solidago spp. and Veronica officinalis L. (Rayment 1965;Penney and McRae 2000). Many of these species may also be found in blueberry fields in Nova Scotia (McCully et al 1991), New Brunswick (Hall 1955(Hall , 1959, and Quebec (Bouchard 1986;Lapointe and Rochefort 2001).…”
mentioning
confidence: 99%